Planting Attitude Responsibility and Concern Through Learning Civics in School Base - Ade Irma Rambe (International Journal of Students Education, 2024)
Literacy culture and citizenship is ability individual and society for act on environment social as part from culture and country. increasing current technology information is very influential interest read student. Research purposes is for explore implementation literacy culture and citizenship in schools base. This study classified into the study qualitative with approach method research used is method naturalistic inquiry. Subjects involved in this study namely 1 head school, 4 teachers, 4 students, and 4 parents. Data collection was carried out use method observations and interviews, with instrument study form sheet interview. After the data is collected, then analyzed with approach qualitative. Research result this is school base has implement literacy culture and citizenship of 80% reviewed from class base aspect, aspect culture school, and community base form activity read 15 minutes every days , borrowing books in the library, planting values characters, there are facility literacy school as well as level involvement team facilitator . Deep advice this study is for all teachers, parents and students more emphasize culture read although constrained with busyness.